Gender disparities in patients treated with veno-arterial ECMO for cardiogenic shock complicating acute myocardial infarction - Qiu, Lingyue; Lin, Yingzhong; Long, Meiying; Li, Qingkuan; Sheng, Xiyong; Shi, Ying; Mo, Changhua; Huang, Qili; Wang, Mengjie; Wu, Xubin; Liu, Ling; Lu, Zhengde; et al. (Frontiers in Cardiovascular Medicine, 2025)
BackgroundIt is crucial to investigate whether there are prognostic disparities among AMI-CS patients undergoing VA-ECMO support. However, there is currently limited data available from China.AimsTo evaluate the gender differences in the characteristics, management, and outcomes among patients with AMI-CS received VA-ECMO support in China.MethodsPatients admitted with AMI-CS at the Chest Pain Center of Guangxi Zhuang Autonomous Region People's Hospital between 2018 and 2023 were included. Sex differences in baseline characteristics, in-hospital management, and outcomes were compared. The primary endpoint was in-hospital mortality. Propensity score matching (PSM) was performed to reduce the impact of baseline clinical differences. Cox regression analysis was conducted to assess the association between gender and in-hospital mortality.ResultsAmong 193 patients presenting with AMI-CS, 15.54% were women. Women were older (67.23 ± 13 vs. 60.37 ± 12.98, p = 0.0028), had a higher prevalence of comorbidities, and a lower proportion of smoking history. Women were less likely to receive vascular reconstruction (70% vs. 88%, p = 0.023), had a significantly shorter duration of ECMO support (2.72 days vs. 4.87 days, p = 0.027), as well as shorter hospitalization days compared to male patients (11.73 ± 10.52 vs. 16.89 ± 10.74, p = 0.026). In-hospital all-cause mortality was notably higher among female patients (90.0%) compared to male patients (71.2%, p = 0.023). However, after PSM, the difference in in-hospital mortality rates between genders was not statistically significant (p = 0.16).ConclusionIn this retrospective study, women were less likely to receive revascularization and exhibited worse in-hospital outcomes compared to men. However, the observed sex difference in in-hospital mortality was attenuated after adjusting for clinical characteristics and acute treatments among AMI-CS patients receiving ECMO support.